Proceedings of the 2016 ACM on International Conference on Multimedia Retrieval 2016
DOI: 10.1145/2911996.2912019
|View full text |Cite
|
Sign up to set email alerts
|

The Science and Detection of Tilting

Abstract: Tilting refers to losing control due to negative emotions, behaving erratically, and thereby suffering adverse consequences.The term tilt originated in poker playing communities, where it is often a consequence of so called bad beats, i.e. losing with an unlikely-to-lose poker hand. Often resulting in devastating monetary losses, tilting is ubiquitous and well known in poker, but rarely studied despite its significance. In this paper, we argue that tilting is a fertile topic for interdisciplinary research both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…I then handed it over to the players and asked them how this relates to them as LoL players and whether they could think of examples of their opponents within these three categories. The players discussed the phenomena of tilt here, which originates from poker, and is a suboptimal state of mind where the individual loses control, impacting decision making, and leading to negative emotions such as anger or frustration (Wei et al, 2016). Some have likened tilt within esports to road rage (White & Romano, 2020).…”
Section: Overcooked and Undercooked Strengthsmentioning
confidence: 99%
“…I then handed it over to the players and asked them how this relates to them as LoL players and whether they could think of examples of their opponents within these three categories. The players discussed the phenomena of tilt here, which originates from poker, and is a suboptimal state of mind where the individual loses control, impacting decision making, and leading to negative emotions such as anger or frustration (Wei et al, 2016). Some have likened tilt within esports to road rage (White & Romano, 2020).…”
Section: Overcooked and Undercooked Strengthsmentioning
confidence: 99%
“…In April of 2019, Open AI Five defeated the world champion DotA 2 team, OG [OpenAI 2019]. Whereas other tilt detection methods have used peripheral equipment to estimate affective states [Wei et al 2016], we use a minimal amount of information to infer effects through user interactions and performance statistics alone, scaling to production with zero user requirements.…”
Section: Related Workmentioning
confidence: 99%
“…Tilt, originating as a poker term, describes a suboptimal state of mind of which can occur after experiencing a significant loss [Palomäki et al 2013], whether a consequence of bad luck, having made a mistake, or a provocating exchange with an adversary. The term has since been adopted in the gaming community [Wei et al 2016], though, the same emotional mechanisms are observed in more universal scenarios, such as in road rage. Tilt in Esports and internet gaming is fairly common, with the general description, nonspecifically related to "emotional breakdown and frustration, due to negative results following hard work", occupying the top position on Urban Dictionary, with the example given citing League of Legends.…”
Section: Introductionmentioning
confidence: 99%